Marital Status As A Predictor of Amnestic Mild Cognitive Impairment in Indonesia - Chandra, Fani Agusta; Darmawan, Octavianus (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2024)
Introduction: Several modifiable risk factors have been identified as the predictors of amnestic mild cognitive impairment (aMCI). However, research focusing on factors beyond biological is limited. Marital status is a psychosocial factor with recognized impact on health that needs further exploration. Objective: This study aimed to evaluate the association between marital status and aMCI amongst older Indonesian population. Material and methods: This was a cross-sectional study of Indonesian Family Life Survey-5. The participants (≥60 years old), excluding individuals with functional dependency, were subdivided into two based on word list recall (WLR) score (cut-off<6.5). Sociodemographic, psychological factors, physical activity, and body mass index were included as predictors. Bivariate and multivariate analyses were conducted. Result: A total of 4287 participants were included. Significant associations were observed between low WLR score and older age, low education, low socioeconomic status, rural residential area, being unmarried, life dissatisfaction, no social engagement, negative affect, and obesity. Multivariate analysis revealed being unmarried was significantly associated with aMCI (AOR 2.38, 95% CI 1.014–5.589, p=0.046), along with older age, low education, low socioeconomic status, and obesity. Discussion: Being unmarried (never married, divorced, or widowed) is a significant predictor of aMCI amongst Indonesian older people. This finding can be explained by the marital resource model and the stress model. Conclusion: This nationwide study is one of the first to explore marital status as a potential yet underexplored factor of aMCI in Indonesia. Being unmarried is associated with an increased risk of aMCI, prompting different approaches in this population.